2008
DOI: 10.1074/jbc.m706626200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Novel Cell Wall Hydrolase CwlT

Abstract: A cell wall hydrolase homologue, Bacillus subtilis YddH (renamed CwlT), was determined to be a novel cell wall lytic enzyme. The cwlT gene is located in the region of an integrative and conjugative element (ICEBs1), and a cwlT-lacZ fusion experiment revealed the significant expression when mitomycin C was added to the culture. Judging from the Pfam data base, CwlT (cell wall lytic enzyme T (Two-catalytic domains)) has two hydrolase domains that exhibit high amino acid sequence similarity to DL-endopeptidases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…Cell wall hydrolases from B. subtilis phage and conjugative elements typically have multiple domains (9,26). CwlT has two domains for peptidoglycan hydrolysis, and each has been characterized biochemically (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell wall hydrolases from B. subtilis phage and conjugative elements typically have multiple domains (9,26). CwlT has two domains for peptidoglycan hydrolysis, and each has been characterized biochemically (9).…”
mentioning
confidence: 99%
“…2) capable of degrading peptidoglycan (9). Peptidoglycan is the major component of the bacterial cell wall and is composed of long carbohydrate chains of alternating amino sugars, N-acetylglucosamine and N-acetylmuramic acid, cross-linked by short peptide chains (10)(11)(12).…”
mentioning
confidence: 99%
“…Because the glutamic acid residue is conserved in all muramidases characterized to date, including CwlP and lytic transglycosylases (such as Slt70), it appears likely that it could be involved in the hydrolytic activity of the enzyme. Nevertheless, Asp 94 of CwlT also appears to be associated with hydrolytic activity, either directly or indirectly (19). However, Weaver et al (24) reported that goose egg-white lysozyme lacks a catalytic aspartic acid residue on the basis of their crystallographic analysis of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the N-terminal domain of CwlT exhibits muramidase activity, and that the critical amino acid residues comprised Glu 87 and Asp 94 (Fig. 4A) (19). In that report, we hypothesized that Glu 87 was the critical amino acid residue controlling hydrolytic activity, because other muramidases such as hen egg-white lysozyme (20,21), bacteriophage T4 lysozyme (22), and goose egg-white lysozyme (23), have a conserved glutamic acid residue in the corresponding position that controls their catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation